The Effect of Capital Intensity on Tax Avvoidance in Manufacturing Companies Listed on The Indonesian Stock Exchange - Fitriani Sardju; Nindah Ayu Letari (Yayasan Riset dan Pengembangan Intelektual, 2022)
This study aims to determine and analyze the Effect of Capital Intensity on Tax Avoidance in manufacturing companies listed on the Indonesian stock exchange. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period. While the samples in this study were chosen based on the purposive sampling method. The data used in this study are secondary data sourced from the published financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The analytical method used is multiple linear regression analysis using SPSS. The results of this study are as follows: Capital Intensity affects tax avoidance.